2013
DOI: 10.4049/jimmunol.1103621
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Promotes Neutrophil Entry into Tumor-Draining Lymph Nodes following Induction of Sterile Inflammation

Abstract: Blood-borne neutrophils are excluded from entering lymph nodes across vascular portals termed high endothelial venules (HEVs) due to lack of expression of the CCR7 homeostatic chemokine receptor. Induction of sterile inflammation increases neutrophil entry in tumor draining lymph nodes (TDLNs), which is critical for induction of anti-tumor adaptive immunity following treatments such as photodynamic therapy (PDT). However, the mechanisms controlling neutrophil entry in TDLNs remain unclear. Prior evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 73 publications
4
71
0
2
Order By: Relevance
“…Accordingly, the IL17-induced CCL-2 and CXCL-2 chemokines, were decreased in tumor supernatants from mice lacking MHCII on pDCs. Decrease in CCL-2 and CXCL-2, which induce the recruitment of lymphocytes, myeloid cells (53)(54)(55), and neutrophils (56), respectively, may explain impaired recruitment of several immune cell populations into tumors in mice lacking MHCII on pDCs. Altogether, our data demonstrated that MHCII þ pDC-derived, tumor-specific Th17 cells increase overall immune tumor infiltrate, including CTLs that would then mediate tumor rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the IL17-induced CCL-2 and CXCL-2 chemokines, were decreased in tumor supernatants from mice lacking MHCII on pDCs. Decrease in CCL-2 and CXCL-2, which induce the recruitment of lymphocytes, myeloid cells (53)(54)(55), and neutrophils (56), respectively, may explain impaired recruitment of several immune cell populations into tumors in mice lacking MHCII on pDCs. Altogether, our data demonstrated that MHCII þ pDC-derived, tumor-specific Th17 cells increase overall immune tumor infiltrate, including CTLs that would then mediate tumor rejection.…”
Section: Discussionmentioning
confidence: 99%
“…These chemokines were all induced in K14.E7 skin after DNCB treatment, However, IL-17A deficiency and suppression of arginase-1 in K14.E7 skin significantly reduced the expression of CXCL1 and CXCL5, suggesting that CXCL1 and CXCL5 are important mediators for IL-17A and arginase to promote the hyperinflammation in K14.E7 skin. Our findings are supported by previous studies that IL-17A promotes neutrophil infiltration via CXCL1 (184) or CXCL5 (185) induction during acute inflammatory responses.…”
Section: Hpv16e7-induced Cutaneous Hyperinflammation To Dncb Is Assosupporting
confidence: 92%
“…This could be related to the IL-17 made by T cells in the draining lymph nodes (SI Appendix, Fig. S13C) following reconstitution of nonspecific transduced neutrophils and, to a lesser extent, FOXO1 knockdown neutrophils, because this cytokine has been shown to promote neutrophil migration into draining lymph nodes (47).…”
Section: Foxo1-deficient Neutrophils Fail To Induce Nit Cells and To mentioning
confidence: 99%